SAFETY CULTURE IN HIGH COMPLEXITY SERVICES IN THE CONTEXT OF THE COVID-19 PANDEMIC - Haas, Luana Elaine; Gaedke, Mari Ângela; Santos, José Augustinho Mendes (Cogitare Enfermagem, 2022)
Objective: to evaluate the patient safety culture in high complexity units of a teaching hospital in times of pandemic. Method: cross-sectional design, carried out in emergency and intensive care units in 2021. We used the self-administered instrument Hospital Survey on Patient Safety Culture with 103 professionals from the multi-professional team. Descriptive analyses and instrument consistency were performed. Results: the strongest areas for patient safety culture were the dimensions teamwork in the unit (79.5%) and expectations and actions of the supervisor/leadership to promote patient safety (73.6%). While the dimensions non-punitive response to error (37.9%) and internal transfers and shift change (31.8%) stood out in the weak areas. A predominance of adverse events underreporting was observed (53.5%). Conclusion: critical sectors, even during the pandemic, showed strengthened areas, although fear of punishment and problems regarding information transfers were highlighted by professionals.